Recommendations for the Management of Construction and Demolition Waste in Treatment Plants - Auxi Barbudo; Jesús Ayuso; Angélica Lozano; Manuel Cabrera; Antonio López-Uceda (Proceedings, 2018)
Construction and demolition waste consists approximately of one third waste generated in the European Union. The recycling of this stream waste will provide ecological and sustainable benefits. Recycled aggregates from construction and demolition waste are clearing a path into civil constructions, as substitutes for natural aggregates. The possible applications of recycled aggregates on infrastructure construction projects will depend on the quality of the recycled aggregates mainly. This will be determined by the nature and the origin of the construction and demolition waste, and the treatment system undergone. Hence, this work proposes recommendations for the handling of construction and demolition waste in treatment plants.